Akibat Hukum Penerapan Restorative Justice Oleh Kejaksaan Pada Perkara Tindak Pidana Penyalahgunaan Narkotika - Naufal Hibatullah, Muhamad; Rusmiati, Elis; Takariawan, Agus (Fakultas Hukum Universitas Islam Malang, 2024)
The Attorney General's Office as a sub-system of the criminal justice system in Indonesia has the authority to conduct restorative justice in narcotics abuse crimes based on Attorney General Guidelines Number 18 of 2021. This research examines the basis and legal consequences of the application of restorative justice by the prosecutor's office for narcotics abuse crimes. This research uses juridical-normative methodology. Through this research, problems were found related to the application of restorative justice, both in terms of legal foundations that do not have conformity between one regulation and another and the legal consequences in the form of a decree of termination of prosecution as a legal product that has no legal remedies. Therefore, it is necessary to evaluate and improve the internal rules of the prosecutor's office related to restorative justice. In addition, the Criminal Procedure Code (KUHAP) needs to be revised to accommodate the application of restorative justice.